Synthesis, Characterization of Titania/Polyaniline/GO Nanocomposites, and Its Photocatalytic Activity Under UV‐Visible Light. Issue 1 (12th June 2018) - Kumar, Azad; Kumar, Ravindra; Pandey, Gajanan
Abstract : In the present study, to prepare the TiO2, TiO2 /PAni, and TiO2 /PAni/GO nanocomposites wet chemical method and they are used as photocatalyst for the photodegradation of Vitoria Blue B dye. The prepared TiO2, TiO2 /PAni, and TiO2 /PAni/GO are subjected to XRD analysis, which gives the information about the presence of phase rutile and anatase both phases are present in the samples. The SEM and TEM of the prepared samples are shown in the particles morphology. The prepared samples are found in nanodiamension. The Photocatalytic degradation of Vitoria Blue B dye is done at different condition of concentration of dye, time of illumination pH, and dose of photocatalyst. The % photodegradation efficiency of Vitoria Blue B dye occur efficiently with TiO2, TiO2 /PAni, and TiO2 /PAni/GO and highest for TiO2 /PAni/GO.